Analgesia induced by the epigenetic drug, L-acetylcarnitine, outlasts the end of treatment in mouse models of chronic inflammatory and neuropathic pain - Notartomaso, Serena (Mol Pain, 2017)
BACKGROUND: L-acetylcarnitine, a drug marketed for the treatment of chronic pain, causes analgesia by epigenetically up-regulating type-2 metabotropic glutamate (mGlu2) receptors in the spinal cord. Because the epigenetic mechanisms are typically long-lasting, we hypothesized that analgesia could outlast the duration of L-acetylcarnitine treatment in models of inflammatory and neuropathic pain. RESULTS: A seven-day treatment with L-acetylcarnitine (100 mg/kg, once a day, i.p.) produced an antiallodynic effect in the complete Freund adjuvant mouse model of chronic inflammatory pain. L-Acetylcarnitine-induced analgesia persisted for at least 14 days after drug withdrawal. In contrast, the analgesic effect of pregabalin, amitryptiline, ceftriaxone, and N-acetylcysteine disappeared seven days after drug withdrawal. L-acetylcarnitine treatment enhanced mGlu2/3 receptor protein levels in the dorsal region of the spinal cord. This effect also persisted for two weeks after drug withdrawal and was associated with increased levels of acetylated histone H3 bound to the Grm2 gene promoter in the dorsal root ganglia. A long-lasting analgesic effect of L-acetylcarnitine was also observed in mice subjected to chronic constriction injury of the sciatic nerve. In these animals, a 14-day treatment with pregabalin, amitryptiline, tramadol, or L-acetylcarnitine produced a significant antiallodynic effect, with pregabalin displaying the greatest efficacy. In mice treated with pregabalin, tramadol or L-acetylcarnitine the analgesic effect was still visible 15 days after the end of drug treatment. However, only in mice treated with L-acetylcarnitine analgesia persisted 37 days after drug withdrawal. This effect was associated with an increase in mGlu2/3 receptor protein levels in the dorsal horns of the spinal cord. CONCLUSIONS: Our findings suggest that L-acetylcarnitine has the unique property to cause a long-lasting analgesic effect that might reduce relapses in patients suffering from chronic pain.